PENGARUH PENDAPATAN KARYAWAN PEMANEN KELAPA SAWIT TERHADAP PENGELUARAN KELUARGA DI AFDELING I DAN AFDELING II DI KEBUN KRUENG LUAS PT AGRO SINERGI NUSANTARA (ASN) - Cut Sri Dewi; Bagio Bagio (Serambi Journal of Agricultural Technology, 2022)
The income of oil palm harvesters is the profit earned from their work at the company where they work. Expenditures for the family of oil palm harvesting employees are expenditures used to meet family needs or improve their standard of living. The purpose of this study was to determine the effect of the income of oil palm harvesters on family expenses in Afdeling I and Afdeling II in Krueng Luas Plantation PT Agro Sinergi Nusantara (ASN). The research method in this research is simple linear regression analysis. The results of this study are the effect of income on expenses for oil palm harvesting employees on family welfare in Afdeling and Afdeling II, Krueng extensive plantations of PT. Agro Sinergi Nusantara (ASN) is calculated based on the income and expenses of all employees at PT. Agro Sinergi Nusantara (ASN) Afdeling I and Afdeling II. Data analysis using a simple linear regression equation with the results calculated using the statistical program (SPSS) temperature of 60 oC and yeast concentration of 6% (S3K3) with the value of each parameter, namely water content 17.55%, color organoleptic test 3.24 (like ) taste 3.28 (like), texture 3.28 (like) and aroma 3.12 (like). Based on the table, it can be seen that the results of the F test calculation can be explained that the Fcount value based on the SPSS calculation is 10.959 with a significant level of 5% and Ftable with a value of 4.28. Then H0 is accepted and H1 is rejected, in other words, the significant probability level is 5%.Keywords: Income, Expenditure, and Employees